PENGARUH MEDIASI PERILAKU ETIS ANTARA KARAKTERISTIK PEKERJAAN DAN PERSONAL VALUES TERHADAP KOMITMEN PROFESIONAL - Andika Ralunan; RAHAYU PUJI SUCI; GUNARIANTO GUNARIANTO (BADAN PENERBITAN UNIVERSITAS WIDYAGAMA, 2022)
ABSTRACT The research aims to describe and analyze the influence of ethical behavior mediation between work characteristics and personal values on professional commitment, with the research subjects of the Primary Tax Service Office Account Representative in Malang City, Kepanjen and Batu. This type of research is explanatory research that uses quantitative methods. The population amounted to 100 Account Representatives and all of them were used as respondents. To prove the hypothesis, the researchers elaborated their calculations using the PLS-SEM model with SmartPLS software version 3.0.The results of the data analysis showed that the higher job characteristics and personal values are able to increase ethical behavior, job characteristics, personal values and ethical behavior that are stronger able to increase professional commitment, stronger personal values work characteristics are able to increase professional commitment mediated by ethical behavior.Keywords: Job Characteristics, Personal Values, Ethical Behavior, Professional Commitment, Account Representative. ABSTRAK Penelitian bertujuan untuk medeskripsikan dan menganalisis pengaruh mediasi perilaku etis antara karakteristik pekerjaan dan personal values terhadap komitmen profesional, dengan subyek penelitian Account Representative Kantor Pelayanan Pajak Pratama di Kota Malang, Kepanjen dan Batu. Jenis penelitian ini adalah penelitian eksplanatori yang menggunakan metode kuantitatif. Populasi berjumlah 100 Account Representative dan keseluruhannya dijadikan sebagai responden. Untuk membuktikan hipotesis, peneliti menguraikan perhitungannya menggunakan model PLS-SEM dengan software SmartPLS versi 3.0.Hasil analisis data menunjukkan bahwa karakteristik pekerjaan dan personal values yang semakin tinggi mampu meningkatkan perilaku etis, karakteristik pekerjaan, personal values dan perilaku etis yang semakin kuat mampu meningkatkan komitmen profesional, karakteristik pekerjaan personal values yang semakin kuat mampu meningkatkan komitmen profesional yang dimediasi perilaku etis.Kata kunci: Karakteristik Pekerjaan, Personal Values, Perilaku Etis, Komitmen Profesional, Account Representative.